Pengujian Toksisitas Akut Oral Dan Dermal pada Biolarvasida Metarhizium anisopliae terhadap Tikus Putih Spraque Dawley - Deni Zulfiana (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2014)
Acute oral and dermal toxicity test against white rats was conducted to determine the toxicity and side effects of bio-larvacide (Metarhizium anisopliae crude extract) on humans. In the oral test used a maximum dose 5000 mg/kg and dermal testing used a maximum dose of 2000 mg/kg. Dose treatment and control tested to 5 Spraque Dawley male rats. The results showed that oral treatment with a dose of 5000 mg/kg did not cause mortality and did not cause changes in anatomic pathology of viceral organs. In the dermal treatment with a dose of 2000 mg/kg did not cause mortality and did not cause changes in anatomic pathology of viceral organs. Based on these results LD50 acute oral M. anisopliae biolarvacide above 5000 mg/kg and the acute dermal is above 2000 mg/kg. It was therefore concluded that the formulation of Metarhizium anisopliae biolarvasida classified as not hazardous when used in accordance with the recommendation of the class I (WHO, 2003).